Condition of the macula in patients with endocrine ophthalmopathology according to optical coherent tomography (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Endocrine ophthalmopathology (EOP) is a progressing chronic disease of the soft tissues of the orbit and eye, developing against the background of the thyroid dysfunction with the unfavorable visual and cosmetic outcome, affecting work able at the age of35—59.Purpose. To investigate a condition of the retina of the macular area in patients with EOP according to the data of optical coherent tomography.Material and methods. Optical coherent tomography (OCT) was made in 103 eyes of 55 patients with EOP by the device « Stratus OCT model 3000 of the firm «Karl Zeis». The results obtained were compared to the data of examination of 69 eyes without ophthalmopathology. The analysis of the data is made with the use of the program Statistics 9.0.Results and their discussion. It was established by OCT that average thickness of the retina in the fovea of the patients with EOP has made (212.8+32.9) pm that was by 18.3pm higher than in the norm (194.5+22.22) pm. The average thickness of the retina around the fovea varied depending on the direction of measurement and was higher than in the norm in all zones and sectors of measurement. Thickness of the macular area of the retina both in the internal and external zones of the investigation in all sectors was authentically higher than in the central one (p
Keywords: endocrine ophthalmopathy; optical Coherence tomography; thickness of the macular; retina